Spontaneous Transition of Double Tachycardias with Atrial Fusion in a Patient with Wolff-Parkinson-White Syndrome - Kim, Dongmin (Korean Circ J, 2016)
Among patients with Wolff-Parkinson-White syndrome, atrioventricular reciprocating tachycardia (AVRT) and atrioventricular nodal reentrant tachycardia (AVNRT) can coexist in a single patient. Direct transition of both tachycardias is rare; however, it can occur after premature atrial or ventricular activity if the cycle lengths of the two tachycardias are similar. Furthermore, persistent atrial activation by an accessory pathway (AP) located outside of the AV node during ongoing AVNRT is also rare. This article describes a case of uncommon atrial activation by an AP during AVNRT and gradual transition of the two supraventricular tachycardias without any preceding atrial or ventricular activity in a patient with preexcitation syndrome.